Efficacy of ozone adjuvant therapy in COVID-19 patients: A meta-analysis study - Jafari-Oori, Mehdi; Vahedian-azimi, Amir; Ghorbanzadeh, Kobra; Sepahvand, Elham; Dehi, Manijeh; Ebadi, Abbas; Izadi, Mortaza (Frontiers in Medicine, 2022)
Introduction: Using ozone therapy to manage COVID-19 patients has been accompanied by conflicting results in prior studies. ‎Therefore, we aimed to widely assess the effects of ozone as adjuvant therapy in COVID-19 patients.‎ Methods: PubMed, Scopus, Web of Science, Cochrane, ProQuest, Springer, and Sage journals were searched systematically until ‎April 2022. Mortality rate, ICU admission, hospital-length stay, negative PCR, pulmonary, renal, and hepatic functions, as well ‎as inflammatory and blood systems were pooled to compare the efficacy of Ozone as adjacent therapy (OZ) and standard ‎treatment (ST). Analyses were run with the random/fixed models, sub-group analysis, funnel plot, and sensitivity analysis using ‎Comprehensive Meta-Analysis (CMA) software version 2.0.‎ Results: The results of four randomized clinical trials (RCTs) and four case-control studies with a total of 371 COVID-19 ‎positive patients were analyzed. The OZ group patients had a shorter length of hospital stay (P > 0.05), lower ICU admissions ‎‎(P > 0.05), and lower mortality rates (P < 0.05) than the ST group cases. After treatment, 41% more COVID-19 patients had ‎negative PCR tests than the ST group (P < 0.05). Serum creatinine and urea levels were not modified in either group (P > 0.05). ‎Moreover, except for albumin serum levels, which decreased significantly in the OZ group, serum bilirubin, ALT, and AST were ‎not modified in either group (P > 0.05). Both arms did not show a decrease in C-reactive protein blood levels (P > 0.05), but the ‎OZ group showed a significant modification in LDH serum levels (P < 0.05). Unlike the d-dimer and WBC serum levels (P > ‎‎0.05), platelet levels were increased in the OZ group (P < 0.05). No negative side effects were demonstrated in either group.‎ Conclusion: Ozone therapy was effective significantly on PCR test and LDH serum levels, as well as mortality based on overall ‎estimation. Concerning the length of hospital stay and ICU admissions, although the results were insignificant, their effect sizes ‎were notable clinically. More RCT studies are needed to show the efficacy of ozone therapy on other studied variables. ‎